A review: environmental consequences of genetically modified (GM) rice / Norzelawati Muhamad - Muhamad, Norzelawati (Faculty of Plantation and Agrotechnology, 2016)
Golden rice is one of the genetically modified variety of Oryza sativa that been transformed to synthesize beta carotene. This GM rice contains vitamin A precursors. Golden rice is not yet been fully commercialized all over the world until recent 2016. This is the results of some objection from different perspective. Some of researchers have found that golden rice have no risk to human well being, no adverse side effects on other organisms and give benefits to environmental consequences. But in addition, some of others researchers have their own explanation that GM rice give impacts and risks to human well being, adverse side effects on other organisms and environmental consequences. A study of environmental consequences of GM rice which need to combine all different opinions from different sources and do research of latest developed GM rice and explore what their uses. Full study about benefits, risks and impacts of GM rice can solved the problem of human well being, adverse side effects on other organisms and environmental consequences.